2019
DOI: 10.2196/14290
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Social Media Use With Physical Activity and Sleep Adequacy Among Adolescents: Cross-Sectional Survey

Abstract: Background Adolescents’ use of social media, which has increased considerably in the past decade, has both positive and negative influences on adolescents’ health and health behaviors. As social media is the most prominent communication tool of choice for adolescents, it is important to understand the relationship between the frequency of social media use and health behaviors among this population. Objective The objective of our study was to examine the associations bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 31 publications
5
61
2
2
Order By: Relevance
“…We provide further support to this relationship by demonstrating that those reporting poor quality of sleep (PSQI index >5) were more likely to use the smartphone. As opposed to this evidence, the results of previous studies comparing the associations between screen time and sleep habits are not consistent [43], probably due to the use of subjective (i.e., daily diaries) measures. Despite this, the time spent on screen devices seems to be correlated with difficulty falling asleep and shorter sleep duration [59] which reinforces the idea of a positive association between screen time and disturbed sleep patterns; however, again, we cannot separate the smartphone usage time from the overall screen time (e.g., TV viewing or computer screen time).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…We provide further support to this relationship by demonstrating that those reporting poor quality of sleep (PSQI index >5) were more likely to use the smartphone. As opposed to this evidence, the results of previous studies comparing the associations between screen time and sleep habits are not consistent [43], probably due to the use of subjective (i.e., daily diaries) measures. Despite this, the time spent on screen devices seems to be correlated with difficulty falling asleep and shorter sleep duration [59] which reinforces the idea of a positive association between screen time and disturbed sleep patterns; however, again, we cannot separate the smartphone usage time from the overall screen time (e.g., TV viewing or computer screen time).…”
Section: Discussioncontrasting
confidence: 88%
“…One of the most interesting findings in the current study suggests that those participants with low levels of physical activity are almost three times more likely to increase the use of smartphones. Previous studies in young adults conducted in the United States have reported that screen time was associated with low levels of subjectively measured physical activity [43]. Specifically, related to the present investigation, research that has tested the relationship of smartphone use and physical activity in college-aged individuals have reported no relationship [29].…”
Section: Discussionmentioning
confidence: 70%
“…Nevertheless, cellphones do have their benefits. When used appropriately, sports applications on smartphones can be used to support and promote physical activity [ 47 , 48 ], but this requires knowledge of what cellphone use is appropriate and an awareness of the benefits of sports to health.…”
Section: Discussionmentioning
confidence: 99%
“…Prema dosadašnjim istraživanjima, preko 90% mladih uzrasta od 13 do 17 godina ima bar jedan profil na bar jednoj društvenoj mreži, dok veliki procenat provodi više od dva sata dnevno na istim [3]. Istraživanje sprovedeno od strane Pju istraživačkog centra (eng.…”
Section: Uvodunclassified